Respuesta :

Answer:

x=-1 and y=-5

Step-by-step explanation:

ሰላም!

Given expressions let them given as two equations

  • y=2+7x....... equation (1)
  • -2x+6y=-28..... equation (2)

Thus, substitute y=2+7x into equation (2)

[tex] - 2x + 6(2 + 7x) = - 28 \\ [/tex]

simplify it

[tex] - 2x + 12 + 42x = - 28 \\ 40x + 12 = - 28[/tex]

subtract 12 from both sides

[tex]40x + 12 - 12 = - 28 - 12 \\ 40x = - 40[/tex]

divide both sides by 40

[tex] \frac{40x}{40} = \frac{ - 40}{40} \\ x = - 1 [/tex]

Therefore, as we get the value of x=-1 substitute it to equation (1) and solve for variable y

[tex]y = 2 + 7x \\ y = 2 + 7( -1 ) \\ y = 2 - 7 \\ y = - 5[/tex]

To be more sure make a cross check on both of the two expressions

Thus,

1) y=2+7x .... substitute y=-5 and x=-1 and check if it is equal

-5=2+7(-1)

-5=2-5

-5=-5

2)-2x+6y=-28... substitute and check

-2(-1)+6(-5)=-28

2-30=-28... (-a)(-b)=ab

-28=-28

Hope it helps!